Logotherapy as a Strategy to Enhance Self-Esteem in Individuals with Disabilities - Fiska Puspa Arinda; Muhammad Miftahul Huda (Asian Journal of Islamic Psychology, 2025)
Self-esteem is a crucial aspect of mental health, often posing challenges for individuals with disabilities. Logotherapy is an effective interventions that can be used to enhance self-esteem, particularly for those who facing physical or psychological limitations. This study aims to evaluate the application of logotherapy in improving self-esteem among individuals with disabilities. This research is a case study approach with a respondent at the Sentra Terpadu “Prof. Dr. Soeharso” Surakarta. Data collection methods included interviews, observations, psychological testing (DAP, BAUM, HTP, Wartegg, SSCT), and self-esteem measurement using the RSES scale. The findings indicate that logotherapy can facilitate positive changes for the respondent, particularly by enhancing self-esteem. Furthermore, the presence of a supportive social environment and appropriate therapeutic interventions reinforces the positive effects of logotherapy. However, potential risks, such as social stigma, must be addressed through psychoeducation to promote broader community awareness and support the empowerment of individuals with disabilities in their social contexts.